An Interdisciplinary Diagnostic Approach to Guide Therapy in C3 Glomerulopathy - Schmidt, Tilman; Afonso, Sara; Perie, Luce; Heidenreich, Karin; Wulf, Sonia; Krebs, Christian F.; Zipfel, Peter F.; Wiech, Thorsten (Frontiers in Immunology, 2022)
Since the re-classification of membranoproliferative glomerulonephritis the new disease entity C3 glomerulopathy is diagnosed if C3 deposition is clearly dominant over immunoglobulins in immunohistochemistry or immunofluorescence. Although this new definition is more orientated at the pathophysiology as mediated by activity of the alternative complement pathway C3 glomerulopathy remains a heterogenous group of disorders. Genetic or autoimmune causes are associated in several but not in all patients with this disease. However, prognosis is poorly predictable, and clinicians cannot directly identify patients that might benefit from therapy. Moreover, therapy may range from supportive care alone, unspecific immune suppression, plasma treatment, or plasma exchange to complement inhibition. The current biopsy based diagnostic approaches sometimes combined with complement profiling are not sufficient to guide clinicians neither (i) whether to treat an individual patient, nor (ii) to choose the best therapy. With this perspective, we propose an interdisciplinary diagnostic approach, including detailed analysis of the kidney biopsy for morphological alterations and immunohistochemical staining, for genetic analyses of complement genes, complement activation patterning in plasma, and furthermore for applying novel approaches for convertase typing and complement profiling directly in renal tissue. Such a combined diagnostic approach was used here for a 42-year-old female patient with a novel mutation in the Factor H gene, C3 glomerulopathy and signs of chronic endothelial damage. We present here an approach that might in future help to guide therapy of renal diseases with relevant complement activation, especially since diverse new anti-complement agents are under clinical investigation.